Editorial: Emerging swine viruses - Perfumo, Carlos Juan; Pereda, Ariel Julian; Jongkaewwattana, Anan; Chen, Zhenhai; Perez, Daniel Roberto; Ma, Jingyun (Frontiers Media, 2021)
Over the last 30 years, diseases caused by emerging swine viruses (ESV) have acquired great relevance, more than in other species. Diseases caused by porcine reproductive and respiratory syndrome virus (PRRSv), high pathogenicity porcine epidemic diarrhea virus (PEDv), porcine circovirus type 2 (PCV-2), and influenza virus H1N1pdm09 had great economic impact. Others, however, such as porcine enteroviruses, porcine toroviruses (PToV), porcine sapelovirus (PSV), porcine bocavirus (PBoV), porcine kobuvirus (PKBV), and porcine Torque teno sus virus (TTSuV) are mostly subclinical in swine herds. Furthermore, novel emerging viruses, such as SENECA virus, atypical porcine pestivirus (APPV), PCV-3, SADS-CoV, influenza D, and others with regional or worldwide distribution constitute a new challenge for researchers and practicing veterinarians.